2003
DOI: 10.1677/erc.0.0100437
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of neuroendocrine and carcinoid tumours.

Abstract: Neuroendocrine tumours (NETs) originate in tissues that contain cells derived from the embryonic neural crest, neuroectoderm and endoderm. Thus, NETs occur at many sites in the body, although the majority occur within the gastro-entero-pancreatic axis and can be subdivided into those of foregut, midgut and hindgut origin. Amongst these, only those of midgut origin are generally argentaffin positive and secrete serotonin, and hence only these should be referred to as carcinoid tumours. NETs may occur as part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
92
0
4

Year Published

2007
2007
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(104 citation statements)
references
References 94 publications
4
92
0
4
Order By: Relevance
“…Because carcinoids of GI origin may originate from midgut or hindgut embryologically (5), the chromosome 11q13 deletion was observed in only one of nine carcinoids of GI origin in our analysis. Our analysis was in agreement with the hypothesis of site-specific difference in the carcinogenesis of bronchial carcinoids and carcinoids of GI origin (14).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Because carcinoids of GI origin may originate from midgut or hindgut embryologically (5), the chromosome 11q13 deletion was observed in only one of nine carcinoids of GI origin in our analysis. Our analysis was in agreement with the hypothesis of site-specific difference in the carcinogenesis of bronchial carcinoids and carcinoids of GI origin (14).…”
Section: Discussionsupporting
confidence: 91%
“…Zhao et al (42) reported on marked genomic imbalance differences between bronchial carcinoids and carcinoids of GI origin. The chromosome 11q13 deletion is a hallmark of multiple endocrine neoplasia type 1 (MEN-1)-related foregut carcinoids and was observed in 5 of 19 bronchial carcinoids in our analysis (13,14). Because carcinoids of GI origin may originate from midgut or hindgut embryologically (5), the chromosome 11q13 deletion was observed in only one of nine carcinoids of GI origin in our analysis.…”
Section: Discussionmentioning
confidence: 77%
“…First, the fact that arginine at AIP codon 16 is a highly conserved amino acid among species (Figure 2), second, from the possibility that an occult pituitary adenoma had been present in the MSS patient in which R16H was identified, one could speculate that such an occult PRL and GH-secreting adenoma may have promoted the breast enlargement, as well as the CRC. Third, the presence of carcinoid tumour in the brother of the MSI R16H-positive patient seems interesting; carcinoids are neuroendocrine tumours, which often occur as part of complex familial endocrine cancer syndromes, such as Multiple Endocrine Neoplasia Type 1 (Leotlela et al, 2003); however, no material was available for segregation studies of the R16H change in this family. Aryl hydrocarbon receptor interacting protein analyses in additional CRC cases and healthy controls would shed light on this possibility, and clarify whether or not R16H is associated with neoplasia.…”
Section: Discussionmentioning
confidence: 98%
“…The molecular mechanisms of WDNTs genesis are poorly understood but have been the focus of many recent reviews (Leotlela et al, 2003;Ö berg, 2005;Zikusoka et al, 2005) and reports of genetic and epigenetic alterations (Serrano et al, 2000;Lubomierski et al, 2001;Chan et al, 2003;Karnik et al, 2005;Wang et al, 2005;Yokoyama et al, 2005;Choi et al, 2007). There are site-specific differences among WDNTs from lung and various subsites of gastrointestinal tract, including clinicopathological features, behavior, and prognosis.…”
Section: Introductionmentioning
confidence: 99%